DAMPAK PEMBELAJARAN DARING TERHADAP HASIL BELAJAR SISWA SD INPRES 6 LOLU - Azizah Thalib; Herlina Herlina; Sri Alvina A Tacaali; Muhammad Aqil (IKIP Siliwangi, 2022)
The aims of this study are, (1) To find out how the implementation of learning in class II SD Inpres 6 Lolu, (2) To find out the benefits of learning from class II SD Inpres 6 Lolu, (3) To find out what efforts are being made by the school during the brave learning in class II SD Inpres 6 Lolu so that the learning process continues. This type of research is a qualitative research with a descriptive approach. Sources of data or research subjects were the principal, teachers, and second grade students of SD Inpres 6 Lolu. The number of students is 28 people. Data collection was done by interview and documentation. The informants in this interview were the principal, and the homeroom teacher for class II SD Inpres 6 Lolu. Based on the results of research conducted in class II SD Inpres 6 Lolu can guarantee the implementation of courageous learning in accordance with applied educational standards and have a good impact on student learning outcomes. Student learning outcomes during bold learning have increased. This is evidenced at the time before learning dared to obtain classical learning completeness of 85.7%. After the implementation of online learning, the classical learning completeness is 100%. Various efforts have been made by the school so that bold learning continues. Such efforts include facilitating the learning process by providing data packages, textbooks, and modules.